Modeling the Magnetic Connection from Earth to Solar Corona during the May 11 Geomagnetic Superstorm - Alessandro Ippolito; Tommaso Alberti; Fabio Giannattasio (The Astrophysical Journal)
In early 2024 May, the solar active region AR 13664 released a series of X-class solar flares and multiple coronal mass ejections (CMEs) that resulted in the strongest geomagnetic storm of the last 20 yr. This study aims at improving our understanding of the magnetic connectivity between Earth and the solar corona by reconstructing the magnetic footpoint of the Earth on the solar surface during this geomagnetic superstorm. A Monte Carlo simulation was applied to model the random walk of interplanetary magnetic field lines due to low-frequency turbulence in the solar wind. This model uses local diffusion coefficients dependent on magnetic fluctuations and the correlation length of solar wind turbulence. The simulation revealed an enhanced diffusion of magnetic field lines due to the passage of CMEs, leading to a broader area of solar surface magnetically connected to Earth, particularly near AR 13664. This proximity facilitated the rapid propagation of solar energetic protons, increasing fluxes observed at L1. The findings have significant implications for predicting space weather effects on Earth and other solar system bodies, contributing to the development of more accurate models for future space exploration missions. Since the Parker spiral reconstruction is consistent with the Magnetic Connectivity Tool, validating the model's reliability, it shows promise for reconstructing magnetic connections for potential real-time purposes.